2015
DOI: 10.4067/s0718-68942015000200004
|View full text |Cite
|
Sign up to set email alerts
|

Arqueología de los colores: Análisis MEB-EDX de mezclas pigmentarias en cerámicas prehispánicas de la cuenca del Río Paraná (Provincia de entre Ríos, Nordeste de Argentina)

Abstract: Se presentan los primeros resultados del análisis fisicoquímico de mezclas pigmentarias rojas y blancas empleadas en la decoración de cerámicas arqueológicas provenientes de sitios localizados en la cuenca media y baja del río Paraná (provincia de Entre Ríos, nordeste de Argentina). El material analizado corresponde a conjuntos cerámicos asociados a grupos Goya-Malabrigo, cronológicamente situados al final del Holoceno Tardío. Se utiliza la técnica MEB-EDX a fin de aportar datos relativos a la caracterización … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
32

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 4 publications
0
5
0
32
Order By: Relevance
“…On the other hand, the high Silicon (203381 ± 8507) ppm and Aluminum (68586 ± 6629) ppm concentrations, in the matrix-paste, identified in the Geochem mode ( Figure 6), indicate that it contains aluminum-silicates, which is usual in clays and pigment mixtures [38]. The results of the NIST2711a standard, in Soil mode, allows to see the precision and exactitude ( Table 3).…”
Section: Red Orange and Brownmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, the high Silicon (203381 ± 8507) ppm and Aluminum (68586 ± 6629) ppm concentrations, in the matrix-paste, identified in the Geochem mode ( Figure 6), indicate that it contains aluminum-silicates, which is usual in clays and pigment mixtures [38]. The results of the NIST2711a standard, in Soil mode, allows to see the precision and exactitude ( Table 3).…”
Section: Red Orange and Brownmentioning
confidence: 96%
“…Usually, kaolinite loses its whitish color, when it contains organic impurities, which would explain the "fugitive white" denomination for that coating. Furthermore, phosphorous could contribute to explain the white color, since it is present in composed elements, such as hydroxyapatite (Ca 5 (PO 4 )) proceeding from bones of diverse origins [38]. Upon comparing the Calcium content (Table 2), between the orange (98435 ppm), red (90882 ppm), fugitive white (89977), brown (52751 ppm) and matrix-paste (52607 ppm) colored pigments, one observes that the BF contains less Calcium than the orange and red, in such a way that Calcium would not be the only origin of the whitish coating.…”
Section: Fugitive White (Bf)mentioning
confidence: 99%
“…These slips are generally better preserved than white pigments, often presenting a cracked appearance. Their application may have involved the addition of a colouring material to the liquid clay, which conceptually can be considered a pre-firing paint (García Rosselló & Calvo Trías 2013;Ottalagano et al 2015;Rye 1981). Studies carried out with XRD identified illite as a potential source of the white colour in some complex tubular artifacts.…”
Section: The Tubular Potterymentioning
confidence: 99%
“…En las últimas décadas, el estudio de pigmentos a partir de diferentes técnicas físico-químicas ha tenido un importante avance en Argentina (López et al 2012), con un mayor desarrollo en la zona del Noroeste (Ottalagano et al 2015). Esta situación se refl eja en un aumento en la cantidad y variedad de técnicas aplicadas a un mismo conjunto y una mayor complejidad en las preguntas de investigación planteadas (López et al 2012).…”
Section: Introductionunclassified
“…Sin embargo, en los últimos años se nota un creciente desarrollo de los estudios arqueométricos también en las regiones del Nordeste y en la región pampeana. Allí se han aplicado diversas técnicas (fl uorescencia de rayos X, difracción de rayos X, espectrometría Raman, entre otras) sobre pigmentos empleados en la alfarería de las zonas de la depresión del Salado (Frère 2015) y en la cuenca media e inferior del río Paraná (Ottalagano et al 2015). Estos estudios refl ejan un proceso de mayor comprensión de la producción y uso de los pigmentos en ambas regiones, y este trabajo se enmarca en este contexto de discusión.…”
Section: Introductionunclassified